Ippaktuq Tasseok ("Harry") carving walrus tusk (Hudson Bay, Canada, area) - Comer, George (Creator); American Museum of Natural History (Creator) (Ownership Statement: Mystic Seaport, 1897)
A bearded Inuit man identified as "Harry" [Ippaktuq Tasseok] is carving a walrus tusk, probably in the Hudson Bay area of the Canadian Arctic. What appear to be tools can be seen hanging on the wall behind him. Lifestyle Livelihood Title supplied by cataloger. Harry is referred to in the North as Comer's [Captain George Comer] "mate," and was the leader of a group of Iglulik Inuit known as the Aivilik or Aivillingmiut . These Inuit of the west coast region of Hudson Bay were closely associated with Comer and the American whalers for many years. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. Slide prepared by the American Museum of Natural History, New York, from an original photograph by Captain George Comer. Slide was used by Comer to illustrate lectures about his Arctic and seafaring experiences.